2009
DOI: 10.1111/j.1467-7687.2009.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in the control of episodic retrieval: an ERP study of recognition memory in children and adults

Abstract: We examined developmental aspects of the ability to monitor the temporal context of an item's previous occurrence while event-related potentials (ERPs) were recorded. In a continuous recognition task, children between 10 and 12 years and young adults watched a stream of pictures repeated with a lag of 10-15 intervening items and indicated recurrences. In a second run, these already familiar pictures were repeated as non-targets along with new pictures, while subjects were instructed to indicate only recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
(96 reference statements)
4
43
1
Order By: Relevance
“…This was the case because both targets and distracters of a new memory set were derived from a pool of the same nine items for both objects (9 shapes) and places (9 places), respectively. Thus, if participants would conceptualize the three memory sets not by color, but by shape because this was the question in the object memory test, this could lead to an enhanced false alarms rate which can occur especially in children (Czernochowski, Mecklinger, & Johansson, 2009;Czernochowski, Mecklinger, Johansson, & Brinkmann, 2005). Moreover, while young children categorize objects holistically, older children abstract feature information (Barrett & Shepp, 1988;Shepp, Barrett, & Kolbet, 1987).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case because both targets and distracters of a new memory set were derived from a pool of the same nine items for both objects (9 shapes) and places (9 places), respectively. Thus, if participants would conceptualize the three memory sets not by color, but by shape because this was the question in the object memory test, this could lead to an enhanced false alarms rate which can occur especially in children (Czernochowski, Mecklinger, & Johansson, 2009;Czernochowski, Mecklinger, Johansson, & Brinkmann, 2005). Moreover, while young children categorize objects holistically, older children abstract feature information (Barrett & Shepp, 1988;Shepp, Barrett, & Kolbet, 1987).…”
Section: The Current Studymentioning
confidence: 99%
“…This strongly suggested that while the anterior activation was more likely to reflect comparisons of familiar or similar objects (familiarity), posterior activation was part of LTM retrieval (recollection). Children show very strong anterior-posterior activations (Czernochowski et al, 2005(Czernochowski et al, , 2009 when distinguishing hits from false alarms. Thus, it is important to control the occurrence of false alarms during children's learning in the novel and repeated conditions.…”
Section: The Current Studymentioning
confidence: 99%
“…There is ample evidence from developmental ERP studies on recognition memory that the parietal repetition effect – the putative ERP correlate of recollection – can be reliably recorded at an early school age (Cycowicz et al, 2003; van Strien et al, 2009), albeit at a longer latency relative to young adults (Czernochowski et al, 2004). However, with respect to the midfrontal FN400 repetition effect – the putative correlate of familiarity – the picture is less clear (Czernochowski et al, 2009; Friedman et al, 2010; Hepworth et al, 2001; Mecklinger et al, 2011). For instance, comparing the ERPs obtained during continuous recognition memory paradigms aimed to assess item and source memory in 10- to 12-year-old children and in adults, Czernochowski et al (2009) found that only adults showed the typical reduction (less negative) of the early frontal negative component for repeated compared to new stimuli; in children, the repetition effect was reversed in polarity (more negative for old than for new items).…”
Section: Introductionmentioning
confidence: 99%
“…However, with respect to the midfrontal FN400 repetition effect – the putative correlate of familiarity – the picture is less clear (Czernochowski et al, 2009; Friedman et al, 2010; Hepworth et al, 2001; Mecklinger et al, 2011). For instance, comparing the ERPs obtained during continuous recognition memory paradigms aimed to assess item and source memory in 10- to 12-year-old children and in adults, Czernochowski et al (2009) found that only adults showed the typical reduction (less negative) of the early frontal negative component for repeated compared to new stimuli; in children, the repetition effect was reversed in polarity (more negative for old than for new items). By contrast, Mecklinger et al (2011) reported that the typical early frontal repetition effect (reduced negativity) could be elicited in 8- to 10-year-old children and adults under speeded response conditions (Mecklinger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether familiar or novel stimuli elicit larger amplitude Nc responses has been inconsistent across studies of infants and young children. Some studies report that novel stimuli elicit a larger negative amplitude Nc response than familiar stimuli (Carver et al, 2003; Czernochowski, Mecklinger, & Johansson, 2009; Dawson, Carver, Meltzoff, Panagiodies, McPartland, & Webb, 2002; Riggins, Rollins, & Graham, 2013), whereas other studies report that familiar stimuli elicit a larger negative amplitude Nc response than novel stimuli (de Haan & Nelson, 1997; 1999; Marshall, Drummey, Fox, & Newcombe, 2002; Riggins, Miller, Bauer, Georgieff, & Nelson, 2009). Due to these inconsistencies, Richards and Reynolds (2005) hypothesized that Nc amplitude “may be greater to the stimulus that elicits the greatest attentional response regardless of novelty versus familiarity or frequency of presentation (p. 612).” A recent study that assessed how visual preference, attention, and stimulus novelty influenced the Nc amplitude in infants supports this hypothesis (Reynolds, Courage, & Richards, 2010).…”
mentioning
confidence: 99%